The clinical method and the evidence-based medicine: some considerations - Arelys Falcón Hernández; Víctor René Navarro Machado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The correct application of the clinical method has diminished all over the world and particularly in Cuba in the last years as a result different issues, including the loss of the doctor-patient relationship, the rejection of the values of physical interrogation and examination and the increasingly irrational and excessive use of medical technology applied to the diagnosis process. The evidence-based medicine is a technical tool to quantify and qualify which data or study is the most accurate, and therefore valid in each case. It helps us clarifying the best way to use and apply "evidence" but it does not replace the clinical method. This article discusses the proper relationship that must be established between the clinical method and the evidence-based medicine in order to provide the appropriate medical care to our patients.